2019
DOI: 10.1002/eat.23035
|View full text |Cite
|
Sign up to set email alerts
|

Is bullying and teasing associated with eating disorders? A systematic review and meta‐analysis

Abstract: Objective Involvement in bullying and teasing has been associated with adverse health outcomes, including eating disorders (EDs). The purpose of this systematic review and meta‐analysis was to examine the association between bullying/teasing and EDs. Method A systematic search was conducted. We included research articles that examined the association between bullying/teasing (victimization and perpetration) and EDs. Studies were required to compare ED cases with a reference group. We performed a qualitative sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
51
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 73 publications
(198 reference statements)
13
51
0
11
Order By: Relevance
“…The evidence grade for ED risk factors is reported in Table 1. Nine meta-analyses 11,12,[54][55][56][57][58][59][60] investigated a wide range of risk factors for ED. Early menarche was investigated in one meta-analysis, peripartum events were investigated in four (APGAR score, C-section, vaginal instrumental delivery, and gestational age lower than 37 weeks), pre-existing medical or psychiatric conditions were investigated in seven (attention deficit and hyperactivity disorder, substance use, type I diabetes), initial psychological features and BMI at baseline assessment in longitudinal studies were investigated in nine, and the remaining investigated risk factors were lifetime or childhood traumatic events or physical, emotional, sexual abuse.…”
Section: Grading the Evidencementioning
confidence: 99%
“…The evidence grade for ED risk factors is reported in Table 1. Nine meta-analyses 11,12,[54][55][56][57][58][59][60] investigated a wide range of risk factors for ED. Early menarche was investigated in one meta-analysis, peripartum events were investigated in four (APGAR score, C-section, vaginal instrumental delivery, and gestational age lower than 37 weeks), pre-existing medical or psychiatric conditions were investigated in seven (attention deficit and hyperactivity disorder, substance use, type I diabetes), initial psychological features and BMI at baseline assessment in longitudinal studies were investigated in nine, and the remaining investigated risk factors were lifetime or childhood traumatic events or physical, emotional, sexual abuse.…”
Section: Grading the Evidencementioning
confidence: 99%
“…Difficulties in social functioning have been identified as key factors in the development and maintenance of AN [2]. For example, before illness onset, individuals with AN report more social difficulties, fewer childhood friends, and engage in more solitary activities than healthy controls (HCs) [3][4][5][6]. During the illness, a variety of difficulties are seen, including high social anxiety, poorer social skills and social problem-solving abilities, loss of interest in social activities, and reduced social networks [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Cybervictimization has been associated with body dissatisfaction and overweight preoccupation [26,46]. Meta-analyses have indicated that avoidance of provocation or bullying is among the main motivators for weight loss [47], and that people with eating disorders were more likely to have been teased about their appearance or bullied prior to the onset of their eating disorder [48].…”
Section: Discussionmentioning
confidence: 99%